Rôle de la formation à la pratique réflexive selon les phases de carrière. Cas des enseignants tunisiens - Mezri Tabka; Mohamed Soudani (Recherches en Éducation)
This work is part of the problem of continuing training of teachers and its role in promoting their professional development. It is the result of exploratory research with a dual, comprehensive and transformative aim, in the Tunisian context. The researcher, playing the role of trainer, designs a continuing training approach inspired by Kolb's experiential model Vacher’s ARPEGE one, which he implements in place of the traditional model provided by the inspector, and in agreement with him. It aims at an initiation to reflexivity as a parameter and indicator of professional development, is based on the experience story, and involves inter- and intra-groups interactions of two groups of teachers with very contrasting levels of expertise, beginners no more than 5 years experienced and others, some of whom have 20 years or more. At the end of the training lasting several half-days, a qualitative approach by group interviews allowed the co-construction of synthetic posters on what they learned. We will present and discuss the preliminary results on how around thirty participants perceived this training, according to their career phases. We will draw out praxeological and heuristic implications.